Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw

Food-grade xylitol production from corncob biomass with acute oral toxicity studies - Dasgupta, Diptarka; Ahuja, Vishal; Singh, Raghuvir; More, Snehal; Mudliar, Sandeep; Kumar, Madan (World Journal of Microbiology & Biotechnology, 2023)
Xylitol, a sugar substitute, is widely used in various food formulations and finds a steady global market. In this study, xylitol crystals were produced from corncob by fermentation (as an alternative to the chemical catalytic process) by a GRAS yeast Pichia caribbica MTCC 5703 and characterized in detail for their purity and presence of any possible contaminant that may adversely affect mammalian cell growth and proliferation. The acute and chronic oral toxicity trials demonstrated no gross pathological changes with average weekly weight gain in female Wistar rats at high xylitol loading (LD50 > 10,000 mg/kg body weight). The clinical chemistry analysis supported the evidence of no dose-dependent effect by analyzing blood biochemical parameters. The finding suggests the possible application of the crystals (> 98% purity) as a food-grade ingredient for commercial manufacture pending human trials.
Keywords: Acute oral toxicity; Corncob; Fermentation; Shelf life analysis; xylitol